Understanding the effects of daily stress on single adults in China - Liu, Heng; Ibrahim, Rahinah; Siti Mastura (Global Academic Excellence, 2024)
During the three-year duration of the COVID-19 pandemic, an increasing number of small and medium-sized enterprises (SMEs) in China have experienced decline in revenues or had to cease operations. Due to the decline in employment opportunities, individuals feel obligated to improve their level of work intensity and pace to maintain existing job opportunities. It is necessary to understand the current social context as well as the various forms and origins of stress among Chinese adults in order to alleviate their daily psychological pressure. This study is part of a larger study in developing happy toys to reduce adults’ stress through passive approach. This paper presents a comprehensive literature review that delves into the social context of China, the various sources of daily stress experienced by Chinese adults, and the consequential effects of such stress on their well-being. Sources of daily stress encompass economic pressure, social isolation, traditional social and cultural pressures, work-related stress, and challenges associated with social ageing, both for men and women. However, societal recognition of the psychological pressure experienced by adults has been inadequate. The findings of this study underscore the correlation between prolonged exposure to stress and the development of various health issues, including insomnia, anxiety, depression, and a range of both physical and mental health conditions, such as compromised immune function. Following an introduction to contextual factors, this article will explore the potential correlation between happy toy and their ability to mitigate the various stressors encountered in an individual’s daily life. The study aims to explore potential pairings of happy toy as a means to alleviate an individual’s daily stressors. This study aims to document the various factors that contribute to the experience of daily stress among single adults in China. Additionally, it seeks to identify the underlying theoretical framework that can inform the development of happy toy specifically designed for Chinese adults with the purpose of alleviating daily stress.